2006
DOI: 10.1108/09513570610679100
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of textual characteristics and company performance in the chairman's statement

Abstract: PurposeThe purpose of this paper is to assess the effect of financial performance on the textual characteristics of the chairman's statement. In particular, given the increased motives for poorly performing management to engage in impression management, the paper focuses on whether companies' reporting strategies depend on underlying financial performance.Design/methodology/approachThe research questions are investigated by examining a range of textual characteristics in the chairman's statements of 100 extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
283
7
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(319 citation statements)
references
References 57 publications
(102 reference statements)
20
283
7
9
Order By: Relevance
“…Examples include Abrahamson and Park (1994), Abrahamson and Amir (1996), Clatworthy and Jones (2003) and Clatworthy and Jones (2006). Similar to some other content analysis techniques, there is a degree of subjectivity involved in this analysis, as it relies upon the classification of keywords into positive and negative categories.…”
Section: Rhetorical Manipulation In Accounting Narrativesmentioning
confidence: 99%
“…Examples include Abrahamson and Park (1994), Abrahamson and Amir (1996), Clatworthy and Jones (2003) and Clatworthy and Jones (2006). Similar to some other content analysis techniques, there is a degree of subjectivity involved in this analysis, as it relies upon the classification of keywords into positive and negative categories.…”
Section: Rhetorical Manipulation In Accounting Narrativesmentioning
confidence: 99%
“…Similarly, Morrow (2005) saw only 14% out of 3.317 company with negative cases coded as weaknesses in MDA. Clatworthy and Jones (2006) agreed that the manager was more selective in the use of narrative in MDA.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the company's financial reporting, impression management is an effort to control and manipulate the impression conveyed to the accounting information users (Clatworthy & Jones, 2006). The manager is supposed to use company reports as a means of impression management to strategically manipulate the perceptions and decisions of stakeholders (Yekini, Wisniewski, & Millo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This tendency holds for companies with deteriorating performance as well as the ones with good results. In their follow up research Clatworthy and Jones (2006) found that the unprofitable companies use fewer personal references, more passive sentences, and focus more on the future in the chairman's statement compared to that by the profitable ones. Aerts (2005) further explores the internal cognitive and external processes that lead to impression management.…”
Section: Textual Information To Automatically Detect Fraudmentioning
confidence: 99%
“…The research of Clatworthy and Jones (2006) showed that by analyzing the chairman's statements of the UK listed companies, profitable companies were more likely to quantify their performance in the text.…”
Section: Descriptive Featuresmentioning
confidence: 99%